METHODICAL TOOLS FOR THE FORECASTING THE ECONOMIC RISKS OF THE AUTOMOTIVE ENTERPRISES IN THE CONDITIONS OF THE STATE STIMULATION OF THE INTERNAL DEMAND FOR THE AUTOMOBILES - I. A. Dmytriiev; I. Yu. Shevchenko; O. I. Dmytriieva; V. V. Maltseva (Фінансово-кредитна діяльність: проблеми теорії та практики, 2019)
Automotive industry is the strategically important part of the industry, which making the significant contribution in the formation of the gross domestic product, the attraction of investments and the creation of workplaces. The world experience of the automotive industry development shows the active participation of the states governments in the formation of the national automobile construction complexes, in particular, in the direction of the state stimulation of the internal demand for the domestic automobiles. At the same time, the growth of the internal demand for the domestic automobiles due to using the state measures creates not only new opportunities for the automotive enterprises, but also new threats. One of these threats is the risk of not receiving the desired economic effect (profit) by the automotive enterprises. The purpose of the article is the development of the methodical tools for the forecasting the economic risks of the automotive enterprises in the conditions of the state stimulation of the internal demand for the automobiles. In the article the methodical tools for the forecasting the economic risks of the automotive enterprises in the conditions of the state stimulation of the internal demand for the automobiles through the calculation of the amount of the expected profit and the level of the optimal economic risk are developed. At the same time, the forecasting the economic risks of the automotive enterprises in the conditions of the state stimulation of the internal demand for the automobiles is proposed to implement in the six variants of the ratio of the initial internal demand for the domestic automobiles, the planned (expected as the result of the state stimulation of the internal demand for the automobiles) demand for the domestic automobiles and the production capacity of the automotive enterprises. It was found out that the factors that cause the increase of the economic risks of the automotive enterprises in the conditions of the state stimulation of the internal demand for the automobiles are: the amount of the variable costs; the amount of the costs for the payment of the personnel labor of the enterprise; the cost of the automotive products; the size of the penalties for the failure to comply with the conditions of the concluded contracts for the production of automobiles; the amount of the capital investments. The factors that contribute to the reducing the economic risk of the automotive enterprises in the conditions of the state stimulation of the internal demand for the automobiles are: the volume of the orders for the automobiles, which was not accepted for the consideration when the planned production indicators were set; the value of the additional internal demand for the automobiles of the domestic production; the level of the income rate.